2022
DOI: 10.1108/ijpdlm-09-2021-0409
|View full text |Cite
|
Sign up to set email alerts
|

Retaining talent in the maritime sector by creating a work-family balance logic: implications from women managers navigating work and family

Abstract: PurposeThis paper contributes to the social pillar of sustainable supply chain management. It does so by investigating how women managers in the maritime sector handle work-family conflict, thereby acting as institutional entrepreneurs to create a work-family balance logic. The maritime sector is a male-dominated supply chain management environment, which suffers from a talent gap of a lack of women executives. One reason for this problem is work-family balance issues that deter women from staying in the workf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…To do so, they explored the sector across the African continent to build the idea of work-family balance logic to discuss talent retention. In this research, Vo et al (2023) demonstrated that female managers act as institutional entrepreneurs due to their self-reflective perspective. For instance, as women needed to work harder than their male colleagues, they needed to create multiple strategies to cope with the conflict between work and family.…”
Section: The Challenge Of Inclusiveness As Transformative Practicesmentioning
confidence: 81%
See 1 more Smart Citation
“…To do so, they explored the sector across the African continent to build the idea of work-family balance logic to discuss talent retention. In this research, Vo et al (2023) demonstrated that female managers act as institutional entrepreneurs due to their self-reflective perspective. For instance, as women needed to work harder than their male colleagues, they needed to create multiple strategies to cope with the conflict between work and family.…”
Section: The Challenge Of Inclusiveness As Transformative Practicesmentioning
confidence: 81%
“…To do so, they explored the sector across the African continent to build the idea of work–family balance logic to discuss talent retention. In this research, Vo et al . (2023) demonstrated that female managers act as institutional entrepreneurs due to their self-reflective perspective.…”
Section: New Frontiers On Critical Perspectives and Transformative Pr...mentioning
confidence: 81%
“…One important aspect is the retention of talent, particularly in the context of work-life balance. Research has shown that creating a work-family balance logic is essential for retaining talent, especially women managers in the shipping sector (Lavissière & Lavissière, 2022). This includes providing support and flexibility to employees to manage their work and personal responsibilities.…”
Section: Talent Management In Shipping Industrymentioning
confidence: 99%